Captain code unleash your coding superpower with Python - Forta, Ben; Forta, Shmuel (Addison-Wesley Professional, 2022)
Becoming a coder is all fun and games! Everyone should learn to code. Much like drawing and sketching, playing an instrument, cooking, or taking pictures and shooting videos, coding is a creative endeavor, which means it's a way to actually create stuff, and creating stuff is incredibly rewarding and satisfying. Sure, it's fun to spend hours on your phone looking at what other people have created; but that's nothing compared to the joy and satisfaction of creating things that other people consume and use. Yep, coding is fun! And if that weren't enough, when you learn to code you develop all sorts of invaluable skills and traits beyond just coding. These include planning, problem solving, communication, logic, empathy, attention to detail, patience, resilience, persistence, and creativity. And it turns out that these skills (especially creativity and creative problem solving) are some of the most in-demand out there. So, coding will help your future career, too, regardless of what that career may be. But, where to start? Captain Code is a welcoming, engaging, and fun introduction to becoming a coder, designed for the young (ages 10-17) and young-at-heart. Experienced educators and coders Ben & Shmuel Forta will guide you using Python, one of the most popular programming languages in the world. You'll learn by creating games, yes, games, from simple projects to retro text-based adventures to complete graphical arcade style games. Captain Code is 400 glossy color pages of goodness packed with welcoming images, useful tips and tidbits, and engaging, readable text that focuses on doing while having fun. All code listings are in full-color and QR codes link to bonus content, downloads, challenge solutions, and more. Captain Code makes coding exciting and rewarding, as it prepares a new generation to take their next steps forwardin education, careers, or both. So, are you ready to unleash your coding superpower and become Captain Code?.